The effects of financial strain on health, morale, and social functioning - Witherspoon, Dennis Robert (Kansas State University, 2017)
Guided by Lazarus and Folkman’s (1984) transactional theory of stress and coping as the theoretical framework, the objective of this research was to determine the association between financial stressors and the outcomes of health, morale, and social functioning. Additionally, the impact of the individual and environment, and the appraisal and coping process were examined. A literature review was conducted based on the theoretical constructs of the individual and environment, stressful events, the appraisal and coping process, morale, social functioning, and health. The sample consisted of 811 individuals age 50 and older, evenly split between males and females, from the 2012 Health and Retirement Study (HRS). Respondents were mostly white, married, and retired. The majority had at least some college and owned a home. Respondents were mainly under the age of 69 and had a mean income of $95,753. The sample reported better than the median scores for morale, social functioning, subjective health, and objective health. Likewise, respondents’ control of finances and mastery scores were also better than the median. However, lower than median scores for financial stressors were reported. OLS regression was utilized to model morale and social functioning while cumulative logistic regression analysis was used to model subjective and objective health. In an effort to model subjective and objective health, morale, and social functioning as one unit, an ad hoc composite measure for all three outcomes was developed which was modeled utilizing cumulative logistic regression. Either full or partial support for some of the hypotheses was indicated. As it pertains to the financial stressor construct, there were some significant relationships with social functioning and morale as theoretically anticipated and hypothesized. Namely, ongoing financial strain was the most frequent variable of significance. However, as a whole, financial stressors were as not as significant under the models as were some of the other variables when modeling the outcomes. Mastery, control over one’s finances, coping behaviors, and positive or negative social support were more frequently significant in the modeling. Control variables of significance often included marital status, gender, education, employment status, income, age, and homeownership status. This research fills a gap by examining the influence of financial stressors individually and simultaneously on physical health, well-being, and social functioning based on a large dataset of secondary data robed in a theoretical framework. By understanding the relationship between financial stress and these outcomes, financial practitioners and educators can develop interventions to promote positive adaptations.
Keywords: Financial stress; Health; Morale; Social functioning; Coping